EXPLORING THE KEY FACTORS SHAPING MENTAL HEALTH IN GEN Z: A SCOPING REVIEW - Amin Aji Budiman; Elok Faradisa; Mira Wahyu Kusumawati; Nadya Karlina Megananda (Community of Publishing in Nursing, 2025)
Generation Z (Gen Z) refers to individuals born between 1997 and 2012. Mental health refers to the emotional, psychological, and social conditions that affect how individuals think, feel, and behave. This generation tends to be independent, creative, unique characteristic and highly socially aware. However, they are also vulnerable to social and mental pressures due to the complex demands of life, which causes Generation Z to face specific challenges affecting their mental health. This scoping review discusses the factors influencing the mental health of Gen Z in the digital era. Articles were searched using databases including ScienceDirect, PubMed, Google Scholar, and ProQuest, focusing on publications from 2021 to 2025. The authors selected and analyzed articles using the PRISMA framework based on predetermined inclusion and exclusion criteria. The search across several electronic databases revealed 538 research articles. After screening, a total of 15 articles were analyzed. The results identified factors influencing the mental health of Gen Z, such as social support (emotional, instrumental, informational, and friendship support), family environment, work-related stress, personal issues, exposure to negative content on social media (including cyberbullying, fake news, and body shaming), online gaming, technology use, and coping mechanisms. Gaining insight into the factors influencing the mental health of Gen Z can help in preventing mental and emotional disorders and support the promotion of overall well-being.